2017
DOI: 10.3390/f8030093
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Canopy Disturbance, Structure, and Species Composition in a Multi-Cohort Hardwood Stand

Abstract: Multi-cohort stands are increasingly recognized and valued because of their biological functioning, biological diversity, and resistance and resiliency to perturbations. These forest ecosystems are epitomized by multiple age classes, and often contain multiple canopy layers, a range of tree size classes, and large amounts of woody debris. Disturbance history reconstructions in multi-cohort stands provide an understanding of the processes that create these systems. In this study, we documented structure and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In fact, in many forest types, more than one intermediate-severity disturbance is likely to occur during the lifespan of the dominant trees. In Quercus stands of the eastern USA for example, the return interval of intermediate-severity disturbance events based on tree-ring records has been found to range from 20-50 years [94][95][96][97][98][99][100]. An intermediate-severity disturbance return interval of ca.…”
Section: How Frequent Are Intermediate-severity Disturbances?mentioning
confidence: 99%
“…In fact, in many forest types, more than one intermediate-severity disturbance is likely to occur during the lifespan of the dominant trees. In Quercus stands of the eastern USA for example, the return interval of intermediate-severity disturbance events based on tree-ring records has been found to range from 20-50 years [94][95][96][97][98][99][100]. An intermediate-severity disturbance return interval of ca.…”
Section: How Frequent Are Intermediate-severity Disturbances?mentioning
confidence: 99%
“…Plants can also impact the spatial pattern of soil resources by altering physical, chemical and biological soil properties [6][7][8]. However, recent studies have found that these interactions and the potential heterogeneity across landscapes could be modified by disturbances [9][10][11]. Wildfire is one of the most important natural ecological disturbance agents in forest ecosystems, is characterized by variations in fire severity and frequency [12,13], and therefore produces spatial and temporal variations in ecological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance history reconstructions using tree-ring records and forest inventory data have been conducted in some oak stands of the eastern USA. The studies have shown that the return interval of disturbance events that removed trees from at least 25% of the stand was typically 20-50 years [6,26,[56][57][58][59][60][61]. Disturbances of this spatial extent and severity would be classified as intermediate-scale events.…”
Section: Intermediate-severity Disturbance Frequencymentioning
confidence: 99%